Intravenous oxytocin bolus and infusion versus infusion alone on the blood loss during caesarean section - Mathe, Priyanka; Kale, Suniti; Batra, Aruna; Batra, Achla; Aggrawal, Shipra; Nagarajappa, Abhishek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: PPH is one of the leading causes of maternal mortality in the world. In India >30% maternal mortality is because of PPH. Methods: 250 females posted for LSCS were randomised into 2 groups. Group A: 5U oxytocin bolus + 40U oxytocin infusion @125 ml/hour in 500 ml saline. Group B: 5 ml Saline bolus + 40 U oxytocin infusion Primary outcome was to measure blood loss (objective and subjective). Secondary outcomes were time for uterine hardening, additional uterotonic agents, hemodynamic changes, side effects and need for blood transfusion within 24 hours of LSCS. Results: Blood loss was significantly less in Group A in objective as well as subjective assessment (p<0.001). Requirement for additional oxytocin bolus was significantly higher in Group B as compared Group A (p=0.025). Postoperative hematocrit of Group A was higher than that of Group B (p<0.001). Transfusion requirement was significantly higher (p=0.04) in Group B (9.6% versus 3.2%). There was no significant difference in hemodynamics between the groups in the intraoperative period (p>0.05). However, during the postoperative period increase in heart rate was noted in Group B (p<0.05). Vomiting was the only major side effect observed, which was higher in Group A (5.6% versus 3.2%). Conclusions: Combination of 5U oxytocin bolus followed by an infusion of 40 U oxytocin given over 4 hours routinely in ASA grade I and ASA grade II parturient significantly decreases the operative blood loss during LSCS without causing any hemodynamic variability. This regimen provides better uterine contractility, lesser need for additional utero-tonic agents and lesser requirement of blood transfusion.